Seasonal Variation in Leaf Growth and Antioxidant Content of Moringa oleifera Cultivated at Buenos Aires, Argentina - Arena, Miriam Elisabet (2016)
The properties and applications of Moringa oleifera are so vast that it is called the "miracle tree". The objective of this work is to study the seasonal variations in the leaf antioxidant content and the scavenging activity on DPPH radicals in concordance with its growth on M. oleifera plants of two seed origin, Commercial (C, seeds that were obtained from a market) and Bolivia (B, seeds that were obtained from a commercial forest of Santa Cruz de la Sierra, Bolivia); the experiment was conducted at Buenos Aires, Argentina. Significant differences were found on leaf growth, antioxidant content and DPPH activity along the growing season. The lower leaf dry weight as percentage of fresh weight, higher specific leaf area, higher relative growth rate and lower phenol content on B leaves than C leaves could indicate that B plants are geared for a higher productivity rate of resource acquisition than C plants. Specific leaf area, leaf dry weight as percentage of fresh weight, phenol content and activity of DPPH radicals on leaf extracts were significantly correlated, which could be used on productivity estimation and nutraceutical valuation. The phenol content and activity of DPPH radicals of leaf extracts of B and C origins indicate that the leaves of the plants growing in the described conditions are of noteworthy value. These are the first antecedents for M. oleifera growing at Buenos Aires, Argentina, allowing to preliminary consider this area as one of the southernmost zone.